PENGARUH KONSENTRASI IBA (Indole Butyric Acid) DAN LAMA PENCELUPAN STEK TERHADAP PERTUMBUHAN GERMINATIF RUMPUT RAJA (Pennisetum purpurephoides) - Ch. W. Patty (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
King grass is parenenial plant that grow slower then elephant grass. The growth and development of the plant breed effected by development of the clone so that some efforts must be taken to stimulate germinative development of king grass. The research purposed to know how for the level of IBA consentration and immersion period of the slip of plant has an effect toward the growth of germination of king grass. Complete randomizet design of factorial type 3 x 3 and Duncan’s multiple range test, were used in the experiment. The treatments were used in the eksperiment: K1 (100 ppm of concentration), K2 (200 ppm of concentration), K3 (300 ppm of concentration), W1 (one hours of immersion period), W2 (two hours of immersion period), W3 (Three hours of immersion period). The result of this research showed that amount the treatments gave significant effect to the percentation of buds, number of buds, height of plant, number of roots, length of root. Nevertheless, there was an inccclination that the more the height of consentration level was given, the result would better than the research. It can be concluded that the level of IBA consentration and immersion period had a positive effect influences which from the average result obtained K3W3 gave the heighest percentation of buds appear, number of buds, height of plant and length of roots. While persentation of buds to appear, number of buds, height of buds and the lowest roots length founded in K1W1.